Competitive Advantage and Policies of Japan’s Electric Vehicles in Southeast Asia - Fadhlia, Maudy Noor; Jaumil, Keefe; Abelechristo, Reuben Vivace; Ilham, Andrian (Journal of World Trade Studies, 2023)
Due to growing environmental awareness, governments and people all over the world started to show concern and place importance on energy efficiency. The transformation from fossil-fuelled energy to renewable energy has been attracting attention and has become the solution that is expected to be more sustainable. This immense potential brings a new idea and innovation for automakers to adopt green technology by creating electric vehicles (EVs). Consequently, the electric vehicle industry has led many automakers, including Japan, to compete in order to dominate the market in Southeast Asia. As one of the longest-running automakers, Japan is unexpectedly left behind and surpassed by other competitors such as China and South Korea. This article aims to identify the policies and strategies Japan implemented to keep up with the competition. The descriptive qualitative method is used to analyse the concept of competitive advantage and government policies. The result shows that Japan implemented both economic and political strategies based on costs and differentiation, as a way to achieve its competitive advantage in the EVs market in Southeast Asia.